Knowledge visualization of performance student based on attendance - Hoe, Jun Sheng (2024)
The project titled "Knowledge Visualization of Student Performance Based on Attendance" represents a multifaceted exploration that merges research and development endeavors. In the contemporary educational landscape, student performance evaluation stands as a pivotal facet of pedagogical improvement. Recognizing the significance of attendance as a determinant of academic success, this project embarks on a comprehensive investigation to analyze, visualize, and enhance the understanding of the intricate relationship between attendance and student performance. The research component of this project involves an in-depth analysis of attendance data collected from diverse educational institutions, encompassing different grade levels and disciplines. Through rigorous statistical analysis and data mining techniques, we aim to uncover meaningful patterns, correlations, and insights that illuminate the impact of attendance on student outcomes. Simultaneously, leveraging the robust features of Power BI, the project translates these findings into interactive, visually-rich dashboards and reports, facilitating a deeper understanding of the attendance-performance relationship. This holistic approach aims to empower educators, administrators, and students with the means to make informed decisions, optimize attendance strategies, and ultimately enhance academic outcomes in the ever-evolving educational ecosystem. Ultimately, the fusion of research and development in this project aims to empower educational stakeholders with actionable insights and practical solutions to enhance student success rates. The knowledge visualization techniques employed will not only shed light on the nuances of attendance's impact but also serve as a catalyst for data-driven decision-making and continuous improvement in educational institutions. In an era characterized by datadriven decision-making, this project represents a crucial step toward the enhancement of educational practices by providing a holistic view of the interplay between attendance and student performance. As we delve into this dynamic intersection of research and development, we envision a future where educational outcomes are optimized through a deeper understanding of the role attendance plays in shaping student success.